2004
DOI: 10.1016/j.femsle.2004.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression, and fibrin (ogen)olytic properties of a subtilisin DJ-4 gene from Bacillus sp. DJ-4

Abstract: Previously, we purified a strong fibrinolytic enzyme (subtilisin DJ-4) from Bacillus sp. DJ-4 and characterized its enzymatic activity. Here, we cloned the gene subtilisin DJ-4, and determines its nucleotide sequence, which showed 97% identity with subtilisin BPN' from B. amyloliquefacens. Recombinant full-subtilisin DJ-4 (rf-subDJ-4) and mature-subtilisin DJ-4 (rm-subDJ-4) were expressed using a pET29 vector system, and their fibrin (ogen)olytic and plasminogen activator activities were studied. rf-subDJ-4 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
6
1
Order By: Relevance
“…This pattern was different from that reported for a fibrinolytic enzyme from B. subtilis, by which the Bβ chain was degraded first [16]. The pattern was also different from that reported for recombinant subtilisin DJ-4, by which the γ-chain was degraded [8]. The detailed degradation pattern for fibrinogen could be different among similar fibrinolytic proteins, and thus each enzyme should be individually characterized for this property.…”
Section: Partial Purification and Properties Of Apre3-17contrasting
confidence: 81%
See 2 more Smart Citations
“…This pattern was different from that reported for a fibrinolytic enzyme from B. subtilis, by which the Bβ chain was degraded first [16]. The pattern was also different from that reported for recombinant subtilisin DJ-4, by which the γ-chain was degraded [8]. The detailed degradation pattern for fibrinogen could be different among similar fibrinolytic proteins, and thus each enzyme should be individually characterized for this property.…”
Section: Partial Purification and Properties Of Apre3-17contrasting
confidence: 81%
“…This phenomenon, so-called "a binding mode," was caused by either the tight binding of enzyme to fibrin in the gel or a high pI value of the enzyme. The same phenomenon was observed for AprE51 [7] and other fibrinolytic enzymes [1,8,15]. Since the calculated pI value of AprE3-17 (6.65) is not high enough to cause this phenomenon, the binding mode might be caused by binding of AprE3-17 to fibrin in the gel.…”
Section: Partial Purification and Properties Of Apre3-17supporting
confidence: 68%
See 1 more Smart Citation
“…This result suggested that the gene hapR of B. velezensis WH-7 was the key protease gene for degrading proteins in tobacco. Previous studies demonstrated that there are different proteases in Bacillus species, such as AprE ( Hata et al, 2001 ; Sareen et al, 2005 ; Shi et al, 2019 ), subtilisin DJ-4 (AY627764) ( Choi et al, 2004 ), DFE (DQ132806) ( Peng et al, 2003 ), BsfA (JN392072.1) ( Hu et al, 2019 ), BAF1 (FJ517584.1) ( Agrebi et al, 2009 ). Herein, the protease HapR was found to be the key protease in B. velezensis for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…Production of fibrinolytic enzymes including nattokinase by expression of them in E. coli has been previously reported [10][11][12], but in most cases they were produced as inactive inclusion bodies or insoluble aggregates, and fibrinolytic active enzymes could only be obtained by renaturation from the inclusion bodies [10,11] or by the IMPACT (Intein Mediated Purification with an Affinity Chintin-binding Tag) system from the insoluble recombinant protein [12].…”
Section: Introductionmentioning
confidence: 99%